2021
DOI: 10.1038/s41598-021-87232-9
|View full text |Cite
|
Sign up to set email alerts
|

The ecological importance of habitat complexity to the Caribbean coral reef herbivore Diadema antillarum: three lines of evidence

Abstract: When Caribbean long-spined sea urchins, Diadema antillarum, are stable at high population densities, their grazing facilitates scleractinian coral dominance. Today, populations remain suppressed after a mass mortality in 1983–1984 caused a loss of their ecosystem functions, and led to widespread declines in ecosystem health. This study provides three lines of evidence to support the assertion that a lack of habitat complexity on Caribbean coral reefs contributes to their recovery failure. Firstly, we extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…However, for corals specifically, depth certainly does not equal refuge, as temperature sensitivity increases with depth (Bongaerts et al, 2017). Furthermore, at the Honduras location, the impacts of grazing herbivores such as Diadema antillarum , which support ecosystem function by reducing algae coverage, thus facilitating coral cover increase, were not considered as a driver of benthic composition in this study despite their known positive impacts (Bodmer et al, 2015, 2021). Our analysis also did not consider prevailing ocean currents, such as the influence of the Banda and Flores Sea (Gordon et al, 1994), which at the Indonesia location, is hypothesized to provide cooling waters to corals of the WNP, potentially alleviating bleaching during thermal stress.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, for corals specifically, depth certainly does not equal refuge, as temperature sensitivity increases with depth (Bongaerts et al, 2017). Furthermore, at the Honduras location, the impacts of grazing herbivores such as Diadema antillarum , which support ecosystem function by reducing algae coverage, thus facilitating coral cover increase, were not considered as a driver of benthic composition in this study despite their known positive impacts (Bodmer et al, 2015, 2021). Our analysis also did not consider prevailing ocean currents, such as the influence of the Banda and Flores Sea (Gordon et al, 1994), which at the Indonesia location, is hypothesized to provide cooling waters to corals of the WNP, potentially alleviating bleaching during thermal stress.…”
Section: Discussionmentioning
confidence: 95%
“…Utila Island is the smallest of the Bay Islands chain and home to a major dive tourism industry and surrounded by a fringing reef ranging from slopes to steeper walls (Andradi-Brown et al, 2016). Finally, Banco Capiro is a recently discovered reef system in the mainland bay of Tela, comprising an offshore bank that is home to an unusually high percentage cover of live coral for the region (Bodmer et al, 2015) and a uniquely high-density population of the keystone herbivorous urchin Diadema antillarum (Bodmer et al, 2021).…”
Section: Survey Locationsmentioning
confidence: 99%
“…However, for corals specifically, depth certainly does not equal refuge, as temperature sensitivity increases with depth (Bongaerts et al, 2017). Furthermore, at the Honduras location, the impacts of grazing herbivores such as Diadema antillarum, which support ecosystem function by reducing algae coverage, thus facilitating coral cover increase, were not considered as a driver of benthic composition in this study despite their known positive impacts (Bodmer et al, 2015(Bodmer et al, , 2021. Our analysis also did not consider prevailing ocean currents, such as the influence of the Banda and Flores Sea (Gordon et al, 1994), which at the Indonesia location, is hypothesized to provide cooling waters to corals of the WNP, potentially alleviating bleaching during thermal stress.…”
Section: Other Drivers Of Reef Compositionmentioning
confidence: 89%
“…All these species, with the exception of H. macrostomum, were frequently observed on the experimental site and Harborne et al (2009) suggested that even a relatively low predation pressure can be sufficient to prevent D. antillarum recovery. It could therefore well be that the predation pressure at the experimental site was too high or the shelter availability too low (Bodmer et al, 2021) to support D. antillarum population recovery, notwithstanding increased settlement due to the streamers.…”
Section: Discussionmentioning
confidence: 99%
“…To select restoration sites with a low predation pressure, it might, paradoxically, be recommended to start ANR outside marine reserves where fishing pressure can reduce predator densities (Edmunds & Carpenter, 2001;Harborne et al, 2009). Alternatively, shallower reefs (Carpenter & Edmunds, 2006;Debrot & Nagelkerken, 2006;Myhre & Acevedo-Gutiérrez, 2007) or reefs with a high shelter availability (Bodmer et al, 2021) might increase post-recruitment survival and increase the chance of successful D. antillarum recovery. Finally, the post-recruitment survival of D. antillarum on locations with a high predation pressure might be enhanced using corrals placed around the streamers, which can protect the juveniles during their first months on the reef (Williams, 2017;Williams, 2022).…”
Section: Discussionmentioning
confidence: 99%